2013
DOI: 10.2139/ssrn.2215763
|View full text |Cite
|
Sign up to set email alerts
|

Employment Duration and Shifts into Retirement in the EU

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Economic modelling has shown that state interventions (e.g. changing eligibility for state pensions, increases to state retirement age [3, 39]) may not be sufficient if people withdraw from the labour market early on health grounds [40]. Public health messages may need to emphasise short and long term consequences of unhealthy behaviour, not just on health but on employment, income and retirement options.…”
Section: Discussionmentioning
confidence: 99%
“…Economic modelling has shown that state interventions (e.g. changing eligibility for state pensions, increases to state retirement age [3, 39]) may not be sufficient if people withdraw from the labour market early on health grounds [40]. Public health messages may need to emphasise short and long term consequences of unhealthy behaviour, not just on health but on employment, income and retirement options.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term sickness absence is a major predictor for all types of exit from the labor market, including unemployment, disability pension (OECD 2010), and early retirement (Aranki and Macchiarelli 2013). The social exclusion process resulting from long-term or chronic illness is strongly mediated by access to paid work.…”
Section: The Value Of Workmentioning
confidence: 99%
“…Through deeper exploration and empirical evidence, the result from Podsakoff (2000) was further tested and developed by Chi-Cheng (2011), who stated that OCB can be measured through dimensions such as: (1) helpfulness, (2) sportiveness, (3) loyalty (4) organizational obedience, (5) individual initiative, (6) citizenship, (7) self-development. Based on assessed evidences through seven dimensions, Baghersalimi (2012) found out that OCB influence on organizational effectiveness, as (1) contributing to team productivity, (2) helping team work and managerial productivity, (3) improving organizational resources efficiency, (4) decreasing employee maintenance fee, (5) improving team work coordination, (6) improving human resources loyalty, and 7improving organizational change adaptability.…”
Section: 2mentioning
confidence: 99%
“…Economic motive and political solidarity among the members of European Union have been scattered by each nation's interest. It threatens the unity of it, as Roman and Greece epic [2].…”
mentioning
confidence: 99%